Outcomes following neonatal cardiac surgery in a South African tertiary centre - Du Toit, Derrik (Department of Paediatrics and Child Health, 2026)
Background: Neonatal Cardiac Surgery has developed significantly since its advent, with improved outcomes, survival, and physiological repair. Limited programs offer neonatal cardiac surgery in emerging economies. We report our experience with neonates undergoing cardiac surgery in our cardiac surgery program. Methods: We performed a secondary data analysis on all neonates aged < 30 days undergoing congenital cardiac surgery from 1 April 2017 to 31 March 2020, including outcomes up to 30-days post-surgery. Results: A total of 859 patients underwent cardiac surgery at our center, of these 81 (9.4%) were neonates. The proportion of neonates increased annually (8.7%, 9.6% and 10.2%). There were 49 (60%) males, and 32 (40%) had surgery in the second week of life. Fourteen (17%) were premature, four (5%) had a major chromosomal abnormality, five (6%) a major medical illness and eight (10%) a major non-cardiac structural anomaly. The RACHS categorization of surgery was predominantly RACHS 3; n = 28 (35%) and 4; n = 23 (29%). Hours in ICU were extensive; median 189 [IQR 114-286] as were hours of ventilation; median 95 [IQR 45-163]. Almost 60% (n=48) of procedures were complicated by sepsis, as defined in our database. The in-hospital mortality rate was 13% (n=13); the 30-day mortality rate was 19.8% (n=16). Conclusion: The proportion of neonates in our service increased over the period. Focused strategies to shorten prolonged ICU stay and decrease rates of bacterial sepsis in neonates are needed. A multi-disciplinary, collaborative heart-team approach is crucial for best outcomes.